2007
DOI: 10.1093/rheumatology/kem022
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal toxic-shock-syndrome-toxin-1 as a risk factor for disease relapse in Wegener's granulomatosis

Abstract: The risk for relapse of WG increases with the presence of tsst-1-positive S. aureus. Eradication of tsst-1-positive S. aureus in WG may show whether disease relapses can be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 24 publications
0
73
1
4
Order By: Relevance
“…A study of 57 patients with WG identified the chronic nasal presence of S. aureus as an independent risk factor for relapse (121), suggesting a role for S. aureus in the cause of ANCA-associated vasculitis. More recently, the presence of nasal S. aureus expressing the superantigen staphylococcal-toxic-shock-syndrome-toxin 1 was identified as a risk factor for relapse in WG (122). CD4 ϩ T cells from the peripheral blood of patients with WG showed reactivity to S. aureus, and a substantial number also recognized PR3, suggesting a role for staphylococci-specific CD4 ϩ T cells in triggering the immune response (123).…”
Section: Introductionmentioning
confidence: 99%
“…A study of 57 patients with WG identified the chronic nasal presence of S. aureus as an independent risk factor for relapse (121), suggesting a role for S. aureus in the cause of ANCA-associated vasculitis. More recently, the presence of nasal S. aureus expressing the superantigen staphylococcal-toxic-shock-syndrome-toxin 1 was identified as a risk factor for relapse in WG (122). CD4 ϩ T cells from the peripheral blood of patients with WG showed reactivity to S. aureus, and a substantial number also recognized PR3, suggesting a role for staphylococci-specific CD4 ϩ T cells in triggering the immune response (123).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the presence of Staphylococcus aureus was accompanied by a higher risk for relapse, while the risk was modulated by the type of SAg, with tsst-1 being most strongly associated with disease relapse. The number of patients positive for Staphylococcus aureus tsst-1 was significantly higher with 36 % compared to the general population [7].…”
Section: The Nasal Microbiome In Granulomatosis With Polyangiitismentioning
confidence: 81%
“…Было установлено, что ре-цидивы ГПА провоцирует носительство в полости носа Staph. aureus [27], и особенно его суперантиген-токсина синдрома токсического шока 1 (toxic shock syndrome toxin 1, TSST-1) [28]. Представлены свидетельства возможной свя-зи продукции АНЦА с другими инфекциями; в частности, АНЦА с различной специфичностью обнаруживали у больных бактериальным эндокардитом (антитела к МПО и ПР3) [29,30], лепрой [31], туберкулезом (антитела к ПР3) [32], эхинококкозом (антитела к МПО и лактоферрину) [33], гепатитом С (антитела к катепсину G) [34], парвови-русом B19 (антитела к МПО и ПР3) [35].…”
Section: Discussionunclassified